Evaluasi Program Kader Remaja Kesehatan Jiwa (Kareja) Puskesmas Gondomanan, Kota Yogyakarta - Lina Handayani; Muhammad Dhimas Alfa-Reza; Aufatcha Ayutya S (Jurnal Kesehatan Masyarakat Indonesia, 2026)
Background: Data results on emotional mental disorders in Yogyakarta, the highest prevalence of permil is in Yogyakarta City at 13.98%, second place is in Gunung Kidul Regency at 13.60%, and third place is in Bantul Regency at 11.19%. The high rate of mental disorders in Yogyakarta Province means that this problem receives special attention from the government, such as programs that can prevent and overcome mental disorders. Method: This research was located at the Gondomanan Community Health Center, Yogyakarta City. This research employed qualitative methods, with a case study approach. Research subjects were recruited using a non-probability sampling technique, namely purposive sampling. The criteria for selecting informants are inclusion and exclusion. Results: The results of the KAREJA program are quite good but still require continuous improvement.  There are still shortages of funds, infrastructure, SOPs, reporting and monitoring in the KAREJA program. Conclusion: There are still deficiencies in the implementation of the KAREJA program so that further evaluation and follow-up regarding the KAREJA program is needed such as funds, infrastructure, SOPs, reporting and monitoring.